Niño Konibo - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a un niño indigena Konibo vistido tradicionalmente usando una vincha y pectoral de mostasilla y monedas de plata.
ENGLISH: A Konibo indigenous child was observed dressed traditionally wearing a headband and pectoral made of mostasilla and silver coins.

SPANISH: Se observó a un niño indigena Konibo vistido tradicionalmente usando una vincha y pectoral de mostasilla y monedas de plata.
ENGLISH: A Konibo indigenous child was observed dressed traditionally wearing a headband and pectoral made of mostasilla and silver coins.
Konibo Child
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Children|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Niños|~|/ Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Children